Antiinflammation Activity of Duku Seed Extract Gel in Carragenan Induced Wistar White Rats - Tyas Hestiningsih; Filzah Framardian Gassani; Trisnawaty K (Sriwijaya Journal of Dentistry, 2022)
Introduction: Inflammation is the body's initial response to tissue damage caused by trauma, exposure to toxins, or infection. Hyaluronic acid was one of the drugs of choice to reduce inflammation due to trauma, but it has side effects. One of the herbal plants that had anti-inflammatory potential was duku seeds. Purpose: The purpose of this study was to determine the anti-inflammatory activity of the duku seed extract gel on male white rats wistar were induced by carrageenan. Method: In vivo study with a pre and post-test control group design was conducted at the Biochemistry Laboratory and Animal House of the Faculty of Medicine Sriwijaya University and Palembang Clinical Laboratory Center. Thirty rats were divided into five groups. Group I, II, and III were treated with 5%, 10%, and 20% duku seed extract gel. Groups IV and V were treated with 0.2% hyaluronic acid gel and a placebo gel, respectively. Rats were induced by 0.1 ml carrageenan solution on the labial gingival of the rat's lower lip and treated with duku seed extract gel twice a day for four days and taking 2 ml of blood from the orbital sinus. The number of neutrophil cells was counted using a hematology analyzer and statistically analyzed.  Results: There was no difference in the number of neutrophil cells before and after treatment in all groups. There was no difference in the number of neutrophil cells after treatment between the extract gel groups and the control. The least increase in neutrophil cells was found in the 20% extract group, but it was not significant. Conclusion: Duku seed extract gel at concentrations of 5%, 10%, and 20% did not have anti-inflammatory activity in male wistar strain rats.